2017
DOI: 10.1093/ckj/sfw120
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia in critically ill patients with acute kidney injury treated with hemodialysis is associated with adverse events

Abstract: Background. Hypophosphatemia in critically ill patients may be exacerbated by renal replacement therapy (RRT). We aimed to identify risk factors and adverse outcomes associated with hypophosphatemia in intensive care patients treated with RRT for acute kidney injury (AKI). Methods. This was a secondary analysis of data from a single-center prospective cohort study of medical and surgical intensive care patients with RRT for AKI between 18 December 2010 and 3 April 2013. Demographic, comorbidity, laboratory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…In contrast, CRRT is associated with a risk of developing hypophosphatemia. Recent studies have linked CRRT‐related hypophosphatemia to adverse outcomes in critically ill patients, including prolonged mechanical ventilation requirements, longer hospital length of stay, and mortality . The approach to managing this complication varies widely among programs, with most centers providing exogenous supplementation while others pre‐emptively add phosphate to existing CRRT solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, CRRT is associated with a risk of developing hypophosphatemia. Recent studies have linked CRRT‐related hypophosphatemia to adverse outcomes in critically ill patients, including prolonged mechanical ventilation requirements, longer hospital length of stay, and mortality . The approach to managing this complication varies widely among programs, with most centers providing exogenous supplementation while others pre‐emptively add phosphate to existing CRRT solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have linked CRRT-related hypophosphatemia to adverse outcomes in critically ill patients, including prolonged mechanical ventilation requirements, longer hospital length of stay, and mortality. [3][4][5] The approach to managing this complication varies widely among programs, with most centers providing exogenous supplementation while others pre-emptively add phosphate to existing CRRT solutions. Both of these practices have been jeopardized in recent years due to shortages of intravenous phosphate solutions.…”
Section: Introductionmentioning
confidence: 99%
“…If depleted and non‐depleted patients are mixed in the intervention, the trial will be assessed as a trial on non‐depleted patients. Since serum levels of magnesium, phosphate and zinc are altered by kidney failure and renal replacement therapy, we will assess the effect of supplements reported in studies with more than 50% of the patients who received renal replacement therapy vs. the effect in studies with fewer patients who received renal replacement therapy. Hypothesised direction of subgroup effect: exaggerated effect of supplementation in patients receiving dialysis, since depletion of the trace elements are common during acute dialysis Effects reported in studies on burns patients only, vs. general ICU patients, due to the excessive shifts in fluids and exudative losses .…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that plasma levels of magnesium or phosphate are associated with need for‐ or duration of mechanical ventilation or length of ICU stay, but other studies failed to reproduce this . Likewise, studies examining associations between plasma zinc and number of organ failures, or associations between low plasma levels of magnesium, phosphate or zinc and mortality have been contradictory . In addition, observational studies examining hypermagnesaemia and hyperphosphataemia have typically reported the inverse association of increased mortality as compared with lower plasma levels …”
Section: Introductionmentioning
confidence: 99%
“…Die Rate der Hypophosphatämie betrug in der ATN-Studie 17,6 % [16], in der RENAL-Studie sogar 65 % [19]. In einigen Zentren gehört daher die Substitution von Phosphat (0,1-0,2 mmol/kg KG/d) zum Routineprotokoll während der Nierenersatztherapie, da bekannt ist, dass Hypophosphatämie die Entwöhnung von der maschinellen Beatmung verlängert [32] und die Sterblichkeit erhöht [33]. Bei Nachweis einer Hypophosphatämie sollte daher neben der Ernährung auch die Antibiotikadosierung überprüft werden.…”
Section: Hypophosphatämie Marker Des Renal Repalcement Traumasunclassified